Echocardiographic Assessment of Cardiac Dysfunction in Patients of Chronic Kidney Disease on Maintenance Hemodialysis - BK, Shyam Kumar; Bassi, S.D.; Sah, Alok Kumar; Acharya, Devendra (Journal of Nepalgunj Medical College, 2019)
Objectives: The Aim of this study to assess and analyze the echocardiographic changes in chronic kidney disease patients on maintenance hemodialysis. Material and methods: We Performed Prospective study of echocardiographic changes in chronic kidney disease (CKD) patients undergoing maintenance hemodialysis at our institute. We performed M-mode echocardiography in 80 CKD patients without obvious clinical evidence of coronary artery disease, Valvular heart disease, congenital heart disease. Data was collected from November 2018 to Nov 2019. Results: 80 Patients Undergoing Hemodialysis were included in our study, out of them Echocardiography finding shown LV dilation and diastolic dysfunction in 39 (48.75%), left ventricular hypertrophy (LVH) in 41 (51.25%), systolic dysfunction and pericardial effusion in 22 (27.5%) and 11 (13.75%) patients respectively. RWMA was present in 10% and Valvular calcification was seen in 5 patients. In sub-group of patients with Hb<10 gm%, LVH was present in 32 (78.05%) vs 9 (21.95%) in patient group with Hb ≥ 10 gm% (p <0.01). Other Sub Group of Patients with BP > 140/90mmhg, LVH Was Present in 34 (82.92%) vs 7 (17.08%) in patients group with BP< 140/90 mm hg (p=0.02). In both sub group p value for systolic dysfunction, RWMA & pericardial effusion is statistically not significant. Conclusion: LV diastolic dysfunction and hypertrophy were most common echocardiographic findings. There was statistically significant correlation between anemia and presence of LVH and positive correlation between presence of hypertension and LVH.